Simplifying
2x + 5 + 6x + -1 = 120
Reorder the terms:
5 + -1 + 2x + 6x = 120
Combine like terms: 5 + -1 = 4
4 + 2x + 6x = 120
Combine like terms: 2x + 6x = 8x
4 + 8x = 120
Solving
4 + 8x = 120
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + -4 + 8x = 120 + -4
Combine like terms: 4 + -4 = 0
0 + 8x = 120 + -4
8x = 120 + -4
Combine like terms: 120 + -4 = 116
8x = 116
Divide each side by '8'.
x = 14.5
Simplifying
x = 14.5